Analisis Faktor-Faktor Keamanan Informasi Perusahaan Dalam Penerapan Bring Your Own Device (BYOD) - Nurillah, Rifda Aisy; Trihandoyo, Agus (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Bring Your Own Device (BYOD) is a phenomenon or an activity where employees in an organization bring their own computer devices to access work. The application of BYOD has advantages in terms of productivity, effectiveness, and flexibility. However, in practice, companies realize that BYOD can increase risks or threats related to information security. This research examines the company’s information security factors that are influenced by Mobile Device Management, information security policy, security culture, and employee training at a banking company in Indonesia. This analysis aims to determine the factors that influence company information security when implementing BYOD. Data collection occurs through questionnaires distributed to employees. Data analysis using the method Partial Least Square (PLS-SEM) with the help of the software SmartPLS. The results of the analysis show that there is an influence between the factors tested in the model, which obtains a value of R-Square that is 0.666. These results can be interpreted as indicating that the independent variables in this study, including Mobile Device Management, information security policies, security culture, and employee training, affect the dependent variable, namely company information security by 66.6%.